2010
DOI: 10.1242/jcs.056465
|View full text |Cite
|
Sign up to set email alerts
|

An exosome-based secretion pathway is responsible for protein export fromLeishmaniaand communication with macrophages

Abstract: SummarySpecialized secretion systems are used by numerous bacterial pathogens to export virulence factors into host target cells. Leishmania and other eukaryotic intracellular pathogens also deliver effector proteins into host cells; however, the mechanisms involved have remained elusive. In this report, we identify exosome-based secretion as a general mechanism for protein secretion by Leishmania, and show that exosomes are involved in the delivery of proteins into host target cells. Comparative quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
548
1
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(581 citation statements)
references
References 41 publications
21
548
1
11
Order By: Relevance
“…It has been reported that cruzipain activity remains in the supernatant of parasite culture medium after high-speed centrifugation at 100,000 × g [57]. Secretome analyses of other trypanosomatids [13,14,38] such as Trypanosoma brucei, Leishmania donovani, and Leishmania major have shown that a large proportion, if not all of the secreted proteins are released as membrane-bound vesicles [5860], similar to mammalian exosomes. Interestingly, in L. donovani, the composition and number of secreted vesicles seems to be regulated by conditions mimicking infection of host cells [60].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cruzipain activity remains in the supernatant of parasite culture medium after high-speed centrifugation at 100,000 × g [57]. Secretome analyses of other trypanosomatids [13,14,38] such as Trypanosoma brucei, Leishmania donovani, and Leishmania major have shown that a large proportion, if not all of the secreted proteins are released as membrane-bound vesicles [5860], similar to mammalian exosomes. Interestingly, in L. donovani, the composition and number of secreted vesicles seems to be regulated by conditions mimicking infection of host cells [60].…”
Section: Discussionmentioning
confidence: 99%
“…We provide evidence that LaSir2RP1 is secreted from both developmental stages of L. amazonensis. Thus, it would be interesting to determine whether LaSir2RP1 is secreted in a soluble form, either inside of or anchored to the membrane of vesicles/exosomes (Silverman et al 2010), since it does not present the classical XDXL motif at the C-terminus, as characteristic for ER/ Golgi resident proteins from protozoa to mammals (Munro and Pelham, 1987;Ilgoutz et al 1999), but was found dispersed in the parasite within vesicle-like structures. Accordingly, the secretory apparatus in parasitic kinetoplastids is organized in a similar way to those in mammalian cells and sequencing of the genes encoding some proteins of the kinetoplastid secretory pathway revealed that the presence of an N-terminal anchor signal is an important feature shared by these proteins (Sakaguchi et al 1992;McConville et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The definition of excreted molecules was rather vague, essentially encompassing all molecules that did not appear to follow classical secretion pathways. In the past few years, however, several parasites have been shown to produce membrane-bound vesicles that increase their chances of survival and transmission [10][11][12][29][30][31][32][33][34]. In theory, there are many ways in which the contents of these vesicles can be delivered to cells within the host.…”
Section: Parasite-derived Vesicles For Long-range Communication Withmentioning
confidence: 99%
“…One is the ability to recruit macrophages to the inoculation site; the other is to stimulate the conversion of arginine to polyamines, which are required for growth of Leishmania, rather than nitric oxide, which activates macrophages and promotes parasite killing [49]. Leishmania promastigotes were among the first examples of parasites that were shown to extrude exosomes in culture [31][32][33]. In common with extracellular vesicles from Trichomonas and T. cruzi, these are enriched for specific fragments of tRNAs and rRNAs [33].…”
Section: Parasite-derived Vesicles For Long-range Communication Withmentioning
confidence: 99%
See 1 more Smart Citation